Research on Bending Rigidity at Flange Connections of UHV Composite Electrical Equipment - Haibo Wang; Yongfeng Cheng; Zhicheng Lu; Zhubing Zhu; Shujun Zhang (Shock and Vibration)
Pillar electrical equipment is an important part of substations. The application of composite materials in pillar equipment can facilitate the improvement of the seismic performance of electrical equipment. In this paper, the test of elastic modulus and bending rigidity was conducted for individual composite elements in insulators and arresters, and the calculation formula for bending rigidity at the composite flange cementing connections was put forward. The numerical simulation model for the earthquake simulation shaking table test of ±1,100 kV composite pillar insulators was established, in which the bending rigidity value for the flange cementing part was obtained by the test or calculation formula. The numerical simulation results were compared with the earthquake simulation shaking table test results, the dynamic characteristics and seismic response of the model were compared, respectively, the validity of the proposed calculation formula for flange bending rigidity of composite cementing parts was verified, and a convenient and effective means was provided for calculating the seismic performance of composite electrical equipment.